The Influence of Multivessel Bypass Surgery on the Onset of Atrial Fibrillation in Elderly Patients - O. A. Rubanenko; A. O. Rubanenko (Столичная издательская компания, 2022)
Aim. To study the factors associated with the development of postoperative atrial fibrillation (POAF) with single- or two- or more vascular bypass grafting in elderly patients with coronary heart disease.Methods. The study included 454 patients with coronary artery disease who underwent CABG. Patients were divided into 4 groups: 1 group - with single-vessel bypass, 2 group - with 2-vessels, 3 group - with 3-vessels and 4 group with 4-vessels bypass. During the observation period postoperative atrial fibrillation (POAF) occurred in 7.5% of patients in group 1, 18.4% in group 2, 17.5% in group 3 and 19.2% of patients in group 4. Since there were no significant differences in the incidence of POAF in patients with 2-4-vessels bypass grafting, these groups were combined for further analysis. 2 groups are allocated: Group I comprised patients with single-vessel bypass graft (79 patients, 76.0% of males, the average age of 65.0 [63.0;68.0] years), Group II - with 2-4-vessels bypass grafts (357 patients, 78.4% of males, the median age of 67.5 [64.5;69.0] years).Results. POAF occurred in 7.5% of patients in group I and in 18.4% of patients in group II (p=0.03) on the median 4.9 [1.2;8.7] day after coronary artery bypass graft. The multivariate regression analysis showed that indicators, associated with POAF development in patients undergoing CABG were the following: aortic cross-clamping time >36 min (odds ratio [OR)]1.4; 95% confidence interval (CI) 1.1-2.8; p=0.030), time of ischemia >19 min (OR 1.7; 95% CI 1.2-3.3; p=0.020), age >65 years (OR 1.8; 95% CI 1,1-4,1; p=0.010), left atrium diameter >39 mm (OR 2.9; 95% CI 1.5-5.4; p=0.005), left ventricular ejection fraction <51% (OR 1.9; 95% CI 1.2-3.0; p=0.04).Conclusion. In our study, atrial fibrillation in the early postoperative period was more common in patients undergoing multivessel coronary bypass surgery. Indicators, significantly associated with POAF in patients undergoing Coronary artery bypass graft were aortic cross-clamping time >36 minutes, time of ischemia >19 minutes, age >65 years, left atrium diameter >39 mm and left ventricular ejection fraction <51%.